Analysis of p2p platform lending - Rolák, Martin; Radová, Jarmila; Rajl, Jiří; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2017)
The subject of this thesis is to map the development of p2p lending in the US. Firstly, we compare the different business models and roles in the current monetary system of commercial banks and p2p platform lenders. The structure as well as trends of p2p lending industry are described. The returns of p2p loans are compared with traditional assets such as bonds, stocks and commodities in the 2011-2016 period. The last part of the thesis examines the loanbook of the most prominent p2p platform lender, Lending Club.
Vedoucí práce: Jarmila Radová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: finance [obor dipl. práce]; diplomové práce; master's theses